Warehouse Order Picking Differences in Bulgarian Enterprises - Dragomirov, Nikolay (Research Papers, 2023)
Warehousing is an important logistics activity related to the management of material flows in the supply chain. To ensure this movement in the warehouses, it is necessary to perform a number of integrated warehouse processes. The order picking process is particularly the most significant, reflecting the whole logistics system. The purpose of the study is to analyze warehousing practices in this field and to define main conclusions. The work presents the results of a survey conducted among Bulgarian trade and manufacturing enterprises, and some of the order picking practices are studied. Based on the data, a number of conclusions are drawn about the practices, especially regarding the application of information systems and technologies. The main focus of the work is the differences between the trade and manufacturing enterprises, as well as their sizes. The main conclusions are related to the correct understanding of the importance of order picking processes and, at the same time, to the insufficient utilization of their potential.